CHEMICAL ATTRIBUTES EVOLUTION OF AN OXISOIL UNDER DIFFERENT TILLAGE METHODS - PAULETTI, Volnei; de LIMA, Marcelo Ricardo; BARCIK, Cristina; BITTENCOURT, Andreia (Scientia Agraria, 2005)
The study evaluated some soil chemical parameters related to the effects of tillage methods in the latter six years. This study was carried out in an OXISOIL, in Ponta Grossa-PR, Brazil. The treatments were: no tillage, conventionally tilled (one plow and two light grates), minimum tillage (two light grates), and soil scarification every three years (during winter). It was used the randomized blocks desing with three replications. The fertilizers were applied, based on soil analysis. Soil samples were taken in 1994 and 2000, in three layers (0-10, 10-20, 20-30 cm), and evaluated for Ca, Mg, K, P, organic C, pH, H + Al. The tillage methods did not show significant effect on pH, H + Al, K and V, among methods in 2000. In the major part of depths and treatments, Mg, K and P increase from 1994 to 2000.